The degree of indicators level violation of local immunity in children with infectious mononucleosis - Bobruk, S. V. (Journal of Education, Health and Sport, 2017)
The article highlights the results of immunological studies of oropharyngeal secretions in 110 children with infectious mononucleosis, aged 1 to 17years who were treated in theVinnytsiaRegionalClinicalInfectiousDiseasesHospitalfrom September to November 2016. The study of the violation of important indicators of local immunity oropharyngeal secretions, such as lactoferrin and interferon-α-I. Research materials served oropharyngeal secret which received no invasive method. This allows you to use this method to determine the degree of immunological disorders in pediatric patients as a criterion to predict treatment efficacy and disease.